Sponsored by: Advertisements as intrusive narratives in Indonesian sinetron - Adila, Wildi; Aini, Lina Nur; Shabrina, Fatiha Rizki; Jeany Prameswary, Yofa Nanda; Febiyanti, Rosa; Amalia, Afika Hany; Mizana, Elza; Retno Sari, Santi; Nurlitasar, Rahma (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
Although an embedded advertisement may not disrupt viewers’ attention to the main narrative fully, some research suggest that this ad is still perceived intrusive. Based on that reason, the present study aimed at investigating the embedded advertisement as micro narratives found in three most watched Indonesian sinetron, Ikatan Cinta, Panggilan, and Bintang Samudra. Advertisements attached in sinetron were classified into three typologies based on how connected they are with the main narrative, including natural, less natural, unnatural. There were two theories underlying this study, namely intrusive narrative from Coe (1986) and intrusive advertisement from Edwards et.al (2002). The current research employed descriptive-qualitative method as the data were in the form of textual and visual elements. The data sources were elicited from the latest episodes of three selected sinetron above from the official application or website and validated through investigator by involving linguistic experts. To analyze the data, the researcher employed a theory by Spradley (1980) that comprises domain analysis, taxonomy analysis, componential analysis, and cultural theme. The results showed that the unnatural advertisement is the most frequent typology appearing in three selected sinetron and is perceived as intrusive as it intrudes on viewers’ accessibility to the sinetron’s content.